Frequency of nursing student medication errors: A systematic review - Triantafyllou, Christos; Gamvrouli, Maria; Myrianthefs, Pavlos (Health & Research Journal, 2023)
Background: Health promotion and patient safety are the main targets of the healthcare provision by the National Health Systems. As for the nursing profession, nursing students make medication errors during clinical interventions, which could be a potential danger to patient safety. The investigation of the frequency of nursing student medication errors, as well as the frequency of each type of nursing student medication errors. Method and Material: A systematic review of the literature was conducted on the electronic database "PubMed" with the keywords: "medication error", "prescribing error", "drug error", "drug use error", "drug mistake", "wrong drug", "wrong dose", "administration error", "dispensing error", "incorrect drug", "incorrect dose", "inappropriate prescribing", "inappropriate medication", "transcription error", "nursing student", "nursing trainee" and on the Greek electronic database IATROTEK-online with the keywords: "medication errors" and "nursing students", without time limit for the publication of scientific papers. On PubMed, the keywords were searched in the title and abstract of the studies. Studies were excluded if they were not published in English and Greek language, were conducted on animals, and were case studies, editorials, and letters to the editor. Results: Of the 47 scientific papers retrieved, 6 were included in the systematic review. A total of 1,904 nursing student medication errors were recorded by nursing students. The majority of errors were: 1) wrong dose form (330,17%), 2) omission error (313, 16.4%), and 3) wrong time (259, 13.6%). Conclusions: The frequency of nursing student medication errors is high. The safe administration of medications is an important skill that nursing students should learn. medication administration.